A generalized possibilistic approach to shell clustering of template-based shapes. Issue 3 (11th February 2017) - Wang, Tsaipei; Hung, Wen-Liang
ABSTRACT: Efficiently and effectively detecting shell-like structures of particular shapes is an important task in computer vision and image processing. This paper presents a generalized possibilistic c -means algorithm (PCM) for shell clustering based on the diversity index of degree- λ proposed by Patil and Taillie [Diversity as a concept and its measurement. J Amer Statist Assoc. 1982;77:548–561]. Experiments on various data sets in Wang [Possibilistic shell clustering of template-based shapes. IEEE Trans Fuzzy Syst. 2009;17:777–793] show that the the proposed generalized PCM performs better than Wang's [Possibilistic shell clustering of template-based shapes. IEEE Trans Fuzzy Syst. 2009;17:777–793] possibilistic shell clustering method according two two criteria: (i) the 'grade of detection' g d for each target cluster; (ii) the amount of computation, denoted as k c, required to attain a given  g d .